Challenges and opportunities in promoting health equity for migrants. (30th September 2020) - Nordström, C; Ingleby, D; Dias, S; Magnus, J; Eikemo, T A; Kumar, B
Abstract: Issue: What has to be done to achieve health equity for migrants? International bodies have published many weighty declarations and recommendations to this end, but these need to be ordered and synthesised. A recurring theoretical problem is how to disentangle the health effects of socioeconomic position (SEP) and migrant status, in order to develop policies that effectively address both factors. Description of the problem: As part of the Policy Framework for Analysis (PFA) for Work Package 7 of the Joint Action on Health Equity Europe (JAHEE), key policy documents between 2007 and 2018 were reviewed to form a 'Road Map' from which a coherent synthesis was extracted. The PFA also developed a model for conceptualising the joint influence of SEP and migrant status. What is the relationship between these, and what policy approaches does it imply? Results: The main recommendations of the 'Road Map' were summarised in two categories: 'upstream' measures (data collection and research, governance, and intersectoral action to tackle social determinants of health) and 'downstream' ones (access to health services, responsiveness to migrants' needs, and attention for vulnerable groups). In the past, 'upstream' measures have been unduly neglected. According to the proposed model, migrant status can have both direct effects on health and indirect ones that are mediated via SEP. Along the indirect pathways, migrants may suffer from increased exposure and/or increased vulnerability to health threats associated with low SEP. Lessons: A high degree of consensus already exists about health inequities affecting migrants and the measures needed to tackle them. The urgent challenge at the moment is to put these conclusions into practice. To this end, there is little point in tackling socioeconomic inequities and those linked to migration and ethnicity as though they had nothing to do with each other. Key messages: The recommendations of international bodies on migrant health from 2007-2018 can be summarized in three 'upstream' measures and three 'downstream' ones. Promoting health equity for migrants requires breaking down the silos in which work on migration and on SEP has hitherto been carried out.